Postcardiotomy Mechanical Circulatory Support in Two Infants with Williams' Syndrome. (11th March 2014) - Contrafouris, Constantinos A.; Chatzis, Andrew C.; Kanakis, Meletios A.; Azariadis, Prodromos A.; Mitropoulos, Fotios A.
Abstract : Supravalvar aortic stenosis (SVAS) in patients with Williams' syndrome is often accompanied by coronary, pulmonary, and even myocardial lesions and therefore associated with increased perioperative morbidity and mortality. Extracorporeal membrane oxygenation (ECMO) provides reliable short-term mechanical circulatory support to patients, especially young, in acute postoperative cardiac failure when conventional means are ineffective. The incorporation of centrifugal pumps in these systems has made their use more efficient and less traumatic. We describe our experience of using the Levitronix CentriMag pump in two patients with Williams' syndrome who underwent surgical correction of supravalvular aortic stenosis.